The Rural Road Map for Action: an examination of undergraduate medical education in Canada - Button, Brenton; Gao, Megan; Dabous, John; Oandasan, Ivy; Bosco, Carmela; Cameron, Erin (Canadian Medical Education Journal, 2023)
Background: There is currently a maldistribution of physicians across Canada, with rural areas facing a greater physician shortage. The taskforce between the College of Family Physicians and the Society of Rural Physicians created a report, “The Rural Road Map for Action” (RRMA) to improve rural Canadians' health by training and retaining an increased number of rural family physicians. Using the RRMA as a framework, this paper aims to examine the extent to which medical schools in Canada are following the RRMA. Methods: Researchers used cross-sectional survey and collected data from 12 of 17 medical school undergraduate Deans from across Canada using both closed and open ended survey questions. Results were analyzed using quantitative (frequencies) and qualitative methods (content analysis). Results: Medical schools use different policies and procedures to recruit rural and Indigenous students. Although longitudinal integrated clerkships offer many benefits, few students have access to them. Leadership representation on decision-making education committees differed across medical schools pointing to a variation in the value of rural physicians’ perspectives. Conclusion: This study illustrated that medical schools are making efforts that align with the RRMA. It is critical they continue to make strategic decisions embedded in educational policy and leadership to reinforce the importance of and influence of rural medical education to support workforce planning.